Oncolytic Adenoviruses: Design, Generation, and Experimental Procedures. (1st July 2013) - Davydova, Julia; Yamamoto, Masato
Abstract: Oncolytic adenoviruses are designed to take advantage of the virus' native ability to replicate in cancer cells to induce oncolysis. Subsequently, the released viral progeny spread and kill the neighboring cancer cells. These characteristics, together with the ability of adenovirus to infect a broad spectrum of cells, its well understood replication machinery, and relative ease of manufacture have led to the intensive use of adenovirus as an anticancer agent. This unit describes cloning strategies, procedures to turn the intended design into virus, and quality analyses of resultant adenoviral vectors. Most of these procedures were optimized especially for oncolytic adenoviral vectors. Curr. Protoc. Hum. Genet . 78:12.14.1‐12.14.21. © 2013 by John Wiley & Sons, Inc.